Legal Analysis of Inconsistencies in the Usage Rights Period Norms for Foreign Nationals in the UUPA & PP Number 18/2021 - Sibuea, Putri Merlin Yoseva (Universitas Negeri Semarang, 2026)
This study aims to analyze the substantive suitability of the provisions of Government Regulation No. 18 of 2021 concerning the 80-year time limit for foreign nationals' Right of Use in the perspective of the basic principles of national agrarian law. Through a normative juridical approach, this study applies a descriptive-prescriptive qualitative analysis to examine the issue in depth in order to determine the proportionality of the time limit to the spirit of the UUPA. The findings show that hierarchically, there is no textual inconsistency between the UUPA and PP No. 18 of 2021 because the UUPA philosophically does not specifically regulate the number of years for Right of Use, so that the stipulation of 80 years is a filling of a technical norm gap that is formally valid. This period has the potential to be inconsistent with the principle of nationality in Article 21 of the UUPA and the character of Right of Use as a temporary right, given that its duration is close to the total validity period of Right of Building Use for Indonesian citizens and allows for de facto control over strategic land through the imposition of Right of Lien. This study recommends harmonizing regulations by proportionally limiting the term of Use Rights for foreign nationals, for example to 45 years as stipulated in Government Regulation No. 40 of 1996, so as to continue providing legal certainty for investment without sacrificing the principles of agrarian justice and the protection of long-term national interests.